KOMITMEN ANTIKORUPSI DALAM PIDATO PRESIDEN PRABOWO: ANALISIS WACANA KRITIS MODEL NORMAN FAIRCLOUGH - Ivan Solihudin; Yudha Surya Nugraha; Jeremias M.de Carvalho (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2026)
The practice of corruption in Indonesia remains highly resilient due to the deeply entrenched influence of the oligarchy within the bureaucracy. Consequently, the president utilizes political communication as a strategic instrument for policy intervention. This study aims to examine the anti-corruption discourse embedded in President Prabowo Subianto's speech delivered on December 24, 2025, with a particular focus on the coinage of the neologism